A fluorescent material and preparation method thereof and micro-nano fluorescent fiber
By developing fluorescent materials TPECNPy-2 and TPECNPy-3 with acid stimulation response and mechanical force stimulation response performance, and preparing micro-nanofluorescent fibers through electrospinning technology, the fluorescence quenching effect and lack of micro-nanofibers are solved in traditional fluorescent materials. The research questions on state have achieved the effect of multiple stimulus response performance and wide application.
Patent Information
- Application Number
- CN202310258074.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-03-16
AI Technical Summary
Traditional fluorescent materials will experience fluorescence quenching effects in aggregation state, which limits their application fields. Most of the existing AIE materials are powder or film states, and there is a lack of research on micro-nanofiber states.
A fluorescent materials TPECNPy-2 and TPECNPy-3 with acid stimulation response and mechanical force stimulation response were developed, and micro-nano fluorescent fibers were prepared by electrospinning technology.
The fluorescent material exhibits good reversibility and multiple stimulus response performance, and can significantly change the fluorescent performance in different external environments, expanding its application range in fields such as smart textiles, flexible wearables and dyeing.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0004130282370000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new materials, and in particular to a fluorescent material and a preparation method thereof, and micro-nano fluorescent fibers. Background Art
[0002] Luminescent materials are widely used in various fields such as biomedicine, semiconductor industry, electronic sensors, and public engineering. As the main carrier of lighting, luminescent materials are an important means of obtaining and displaying information in the information age. Various new technologies and methods are used in different daily work of human beings, and it is necessary to develop multifunctional luminescent materials with different characteristics and components. Among luminescent materials, fluorescent materials have the characteristics of high sensitivity, low cost and wide application fields, but traditional fluorescent materials will have fluorescence quenching effect (aggregation-caused quenching, ACQ), that is, when the molecules appear in an aggregated state, the fluorescence will weaken or even quench. The ACQ effect greatly limits the application field of its aggregated state. In 2001, a new fluorescent material was reported. This type of material has weak or even almost no fluorescence in solution, but can emit strong fluorescence in solid state. This type of material is called aggregation-induced emission (AIE) material. AIE material solves the ACQ problem of traditional fluorescent materials and has developed rapidly in the past two decades. Among AIE materials, stimulus-responsive materials can significantly change their fluorescence properties under the influence of external environment (mechanical force, temperature, light, pH, etc.). Therefore, there are a large number of reports on AIE stimulus-responsive materials in the fields of fluorescence sensors, optoelectronic devices, and biomedicine. Multi-stimulus-responsive materials are materials that have two or more stimulus-responsive properties at the same time. This type of material has higher requirements for its structure, so there are relatively few reports.
[0003] In addition, most of the AIE aggregation-inducing materials reported so far are in powder or film state, and relatively few are in micro-nanofiber state. Therefore, it is of great significance to find a new type of AIE molecular fluorescent material for the preparation of micro-nanofiber fluorescence. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a fluorescent material having acid stimulation responsiveness and mechanical force stimulation responsiveness and good reversibility.
[0005] The invention also provides a method for preparing the fluorescent material.
[0006] The invention also provides a micro-nano fluorescent fiber containing fluorescent material.
[0007] The invention also provides a method for preparing the micro-nano fluorescent fiber.
[0008] A first aspect of the present invention provides a fluorescent material, the fluorescent material comprising at least one of TPECNPy-2 and TPECNPy-3;
[0009]
[0010] The fluorescent material according to the first aspect of the present invention has at least the following beneficial effects:
[0011] The two fluorescent materials TPECNPy-2 and TPECNPy-3 of the present invention both show acid stimulation responsiveness and mechanical force stimulation responsiveness and have good reversibility.
[0012] According to some embodiments of the present invention, the TPECNPy-2 emits blue-green light, and the maximum emission wavelength of solid-state fluorescence is 476-482 nm.
[0013] According to some embodiments of the present invention, the TPECNPy-2 emits blue-green light, and the maximum emission wavelength of solid-state fluorescence is about 479 nm.
[0014] According to some embodiments of the present invention, the TPECNPy-3 emits light blue light, and the maximum emission wavelength of solid-state fluorescence is 471-477 nm.
[0015] According to some embodiments of the present invention, the TPECNPy-3 emits light blue light, and the maximum emission wavelength of solid-state fluorescence is 474 nm.
[0016] The second aspect of the present invention provides a method for preparing the above fluorescent material, comprising the following steps:
[0017] Tetraphenylethylene aldehyde (P4A) is mixed with a pyridine source and reacted under the catalysis of tetrabutylammonium hydroxide.
[0018] The method for preparing the fluorescent material according to the second aspect of the present invention has at least the following beneficial effects:
[0019] The fluorescent material prepared by using tetraphenylethylene aldehyde and pyridine source as raw materials exhibits acid stimulation responsiveness and mechanical force stimulation responsiveness and has good reversibility. The fluorescent material of the present invention can be further applied to the fields of fluorescent probes and the like.
[0020] The yield of the fluorescent material prepared by the preparation method of the present invention is 70-80%.
[0021] According to some embodiments of the present invention, the molar ratio of P4A to the pyridine source is about 1:1 to 1.2, for example, about 1:1.15.
[0022] According to some embodiments of the present invention, the mass ratio of P4A to the pyridine source is 360:118.
[0023] According to some embodiments of the present invention, the pyridine source includes at least one of 2-acetonitrilepyridine and 3-acetonitrilepyridine.
[0024] Tetraphenylethylene monoaldehyde has a simple synthesis, typical AIE functional group, and high fluorescence quantum efficiency. Pyridine contains heteroatoms, and its combination with tetraphenylethylene may produce photophysical properties and push-pull electron effects.
[0025] According to some embodiments of the present invention, the amount of tetrabutylammonium hydroxide is 0.1-0.5 ml.
[0026] Preferably, the amount of tetrabutylammonium hydroxide used is 0.5 ml.
[0027] According to some embodiments of the present invention, the method for preparing the fluorescent material further comprises, after the reaction, filtering the obtained mixture under reduced pressure, washing the obtained solid with ethanol, and then drying.
[0028] According to some embodiments of the present invention, in the washing, the amount of ethanol used is 10 to 100 times the sum of the masses of the P4A and the pyridine source.
[0029] According to some embodiments of the present invention, the drying temperature is 100° C. and the drying time is 24 hours.
[0030] According to some embodiments of the present invention, the reaction is carried out under stirring for 6 to 24 hours.
[0031] The third aspect of the present invention provides a micro-nano fluorescent fiber containing a fluorescent material, wherein the raw materials for preparing the micro-nano fluorescent fiber include the fluorescent material.
[0032] The micro-nano fluorescent fiber according to the third aspect of the present invention has at least the following beneficial effects:
[0033] Since the micro-nano fluorescent fiber adopts the fluorescent material, it at least has all the effects of the fluorescent material.
[0034] According to some embodiments of the present invention, raw materials for preparing the micro-nano fluorescent fibers further include cellulose acetate and a solvent.
[0035] According to some embodiments of the invention, the solvent comprises dimethylformamide (DMF) and dichloromethane (DCM).
[0036] According to some embodiments of the present invention, the mass ratio of DMF to DCM is 1:2.
[0037] The fourth aspect of the present invention provides a method for preparing the micro-nano fluorescent fiber containing fluorescent material, comprising the following steps:
[0038] The fluorescent material, cellulose acetate and solvent are mixed to form a spinning solution, and micro-nano fluorescent fibers are prepared by electrostatic spinning technology.
[0039] The method for preparing micro-nano fluorescent fibers according to the fourth aspect of the present invention has at least the following beneficial effects:
[0040] Electrospinning is an effective method to obtain polymer-based micro-nano fiber films. Compared with cast films, micro-nano fiber films show larger specific surface area and higher porosity. The fluorescent film made by electrospinning can effectively improve the sensitivity and response rate. Through the electrospinning process, AIE multi-stimulus responsive materials and polymers that are easy to fiberize are compounded to prepare AIE multi-stimulus responsive micro-nano fibers, thereby expanding its application in smart textiles, flexible wearables, dyeing and finishing, and improving its response sensitivity and reducing the detection limit.
[0041] The fluorescent material prepared by the present invention is compounded with a polymer, and micro-nano fluorescent fibers are prepared by electrostatic spinning technology, which provides ideas and methods for preparing a new type of fluorescent micro-nano fiber sensor.
[0042] According to some embodiments of the present invention, the added amount of the cellulose acetate is 13% to 20% of the total mass ratio of the spinning solution.
[0043] Preferably, the added amount of the cellulose acetate is 17% to 20% of the total mass ratio of the spinning solution.
[0044] More preferably, the added amount of the cellulose acetate is 19% of the total mass ratio of the spinning solution.
[0045] If the amount of cellulose acetate added is too low as the total mass ratio of the spinning solution, the spinning effect is poor. If the amount of cellulose acetate added is too high as the total mass ratio of the spinning solution, the solution viscosity is too high, which easily clogs the needle and makes it difficult to spray out evenly, resulting in poor spinning effect or even no spinning.
[0046] According to some embodiments of the present invention, the added amount of the fluorescent material is 1% by mass of the cellulose acetate.
[0047] According to some embodiments of the present invention, the spinning voltage of the electrospinning technology is 13KV to 17KV.
[0048] Preferably, the spinning voltage of the electrospinning technology is 13KV.
[0049] According to some embodiments of the present invention, the propulsion rate of the electrospinning technology is 1 mL / h to 2 mL / h.
[0050] Preferably, the propulsion rate of the electrospinning technology is 1 mL / h.
[0051] According to some embodiments of the present invention, the curing distance from the electrospinning needle to the receiving screen is 10 to 15 cm.
[0052] Preferably, the curing distance from the electrospinning needle to the receiving screen is 15 cm.
[0053] According to some embodiments of the present invention, the spinning time of the electrospinning technology is 2 to 3 hours.
[0054] Preferably, the spinning time of the electrospinning technology is 2 hours.
[0055] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.
[0056] Other features and advantages of the present invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0058] Figure 1 The synthetic route of the preparation method described in Example 1 and Example 2 of the present invention;
[0059] Figure 2 The fluorescence peak intensity change of the fluorescent material of the present invention in water / THF mixed solutions with different water contents;
[0060] (a) TPECNPy-2; (b) TPECNPy-3.
[0061] Figure 3 The UV-visible spectra of the fluorescent material of the present invention in water / THF mixed solutions with different water contents;
[0062] (a) TPECNPy-2; (b) TPECNPy-3.
[0063] Figure 4 The fluorescence peak intensity change of the fluorescent material of the present invention;
[0064] (a) TPECNPy-2; (b) TPECNPy-3.
[0065] Figure 5 The fluorescent photos of the fluorescent material of the present invention when the water content is 0% and 90% under 365nm ultraviolet light irradiation;
[0066] (a) TPECNPy-2; (b) TPECNPy-3.
[0067] Figure 6 (a) is a photo of the original TPECNPy-2 sample under 365nm ultraviolet light (left) and a photo of the ground TPECNPy-2 sample under 365nm ultraviolet light (right);
[0068] (b) is a photo of the original TPECNPy-3 sample under 365nm ultraviolet light (left) and a photo of the ground TPECNPy-3 sample under 365nm ultraviolet light (right);
[0069] (c) is the change of the maximum emission wavelength of TPECNPy-2 fluorescence, (o) original sample, (g) ground sample, (f) solvent fumigated ground sample (the ground sample of the compound was fumigated in dichloromethane vapor for 1 h), (e) annealed ground sample (the ground sample of the compound was annealed at 120 ° C for 1 h);
[0070] (d) Changes in the maximum fluorescence emission wavelength of TPECNPy-3, (o) original sample, (g) ground sample, (f) solvent fumigated ground sample (the ground sample of the compound was fumigated in dichloromethane vapor for 1 h), (e) annealed ground sample (the ground sample of the compound was annealed at 120°C for 1 h).
[0071] Figure 7 (a) is the PL spectrum and fluorescence photograph of TPECNPy-2 powder under external stimulation (365nm UV light);
[0072] (b) PL spectrum and fluorescence photo of TPECNPy-3 powder under external stimulation (365nm UV light);
[0073] (c) Changes in the maximum emission wavelength of TPECNPy-2 fluorescence, (O) original sample, (O-HCl) original sample acid-fumigation, (O-HCL-NH3) original sample acid-fumigation followed by alkaline-fumigation;
[0074] (d) The change of the maximum emission wavelength of TPECNPy-3 fluorescence, (O) original sample, (O-HCl) original sample acid-fumigated, (O-HCL-NH3) original sample acid-fumigated and then alkaline-fumigated.
[0075] Figure 8(a) is a fluorescent photo of the compound TPECNP-2 powder (365nm UV light);
[0076] (b) is a fluorescence photograph of compound TPECNP-3 (365nm UV light);
[0077] (c) is the PL spectrum of compound TPECNP-2 powder under external stimulation, (G) the sample after grinding, (G-HCl) the sample after acid fumigation after grinding, (G-HCL-NH3) the sample after acid fumigation and alkaline fumigation after grinding;
[0078] (d)(c) are PL spectra of compound TPECNP-3 powder under external stimulation, (G) sample after grinding, (G-HCl) sample after acid fumigation after grinding, (G-HCL-NH3) sample after acid fumigation and then alkaline fumigation after grinding.
[0079] Fig. 9 The fluorescence spectra of the micro-nano fluorescent fiber film of this application after being treated under different conditions;
[0080] (a) TPECNPy-2; (b) TPECNPy-3.
[0081] Fig.10 This is the fluorescence photograph of the TPECNP-2 micro-nano fluorescent fiber film of this application under 365nm ultraviolet light after being treated under different conditions;
[0082] (m) original membrane, (mh) nanofiber membrane fumigated with hydrogen chloride gas, (mhn) nanofiber membrane fumigated with ammonia vapor after hydrogen chloride gas fumigation;
[0083] Fig.11 This is the fluorescence photograph of the TPECNPy-3 micro-nano fluorescent fiber film of this application under 365nm ultraviolet light after being treated under different conditions;
[0084] (m) original membrane, (mh) nanofiber membrane fumigated with hydrogen chloride gas, and (mhn) nanofiber membrane fumigated with ammonia vapor after hydrogen chloride gas fumigation.
[0085] Fig.12 The mass spectrum of TPECNPy-2 prepared by the preparation method of Example 1 of the present invention;
[0086] Fig.13 The mass spectrum of TPECNPy-3 prepared by the preparation method of Example 1 of the present invention; DETAILED DESCRIPTION
[0087] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0088] Fluorescence spectrometer: Shimadzu RF-6000, Japan Shimadzu Corporation.
[0089] UV-visible photometer: SHIMADZU / UV-2700, Shimadzu Corporation, Japan.
[0090] Nuclear magnetic resonance spectrometer: Bruker AVANCE-500.
[0091] Mass spectrometer: Aglient 6550 QToF & Thermo Fisher-QE.
[0092] Electrospinning machine: E02; Foshan Light Industry Co., Ltd.
[0093] Example 1
[0094] The present invention provides a method for preparing a fluorescent material TPECNPy-2, comprising the following steps:
[0095] Weigh tetraphenylethylene monoaldehyde (2.00 g, 5.54 mmol; CAS: 1289218-74-1) and 2-acetonitrile pyridine (0.74 g, 6.38 mmol, CAS: 2739-97-1) in a three-necked flask and dissolve them. Add 40 mL of ethanol to fully dissolve them. Add 0.05 ml of tetrabutylammonium hydroxide (0.8 M methanol solution, CAS: 2052-49-5) and stir to react for 6 hours. Stop the reaction, filter under reduced pressure, wash the product with ethanol 3 times until the washing liquid is relatively clear, scrape off the sample powder and put it in an oven to dry. Finally, weigh 2.15 g of light yellow solid, with a yield of 78.5%. The synthetic route of the fluorescent material in this embodiment is as follows: Figure 1 As shown in the mass spectrum Fig.12 As shown, the test results of the product obtained in this embodiment are: 1 H NMR (600MHz, DMSO-d6) δ8.69–8.57(m,1H),8.33(s,1H),7.94(td,J=7.8,1.8Hz,1H),7.81( dd,J=10.1,8.0Hz,3H),7.43(dd,J=7.5,4.8Hz,1H),7.25–7.08(m,11H),7.07–6.91(m,6H).
[0096] 13 C NMR (151MHz, DMSO-d6) δ151.61,150.10,146.93,144.72,143.31,143.27,143.11,142.43,140.17,138.28,131.81,131. 59,131.20,131.15,131.07,129.73,128.52,128.47,128.32,127.44,127.29,127.26,124.34,121.01,118.00,110.38.
[0097] EI-MS,m / z:460([M] + ,calcd for C 34 H 24 N2,460). It can be seen that the fluorescent material shown in Formula I was prepared in this embodiment.
[0098] Example 2
[0099] This embodiment provides a method for preparing micro-nano fluorescent fibers using TPECNPy-2 prepared in Example 1 as a preparation raw material, the steps are:
[0100] Prepare a spinning solution containing TPECNPy-2 sample: weigh DMF:DCM=1:2 as solvent, add 19% of cellulose acetate powder to dissolve, and completely dissolve the prepared solution in a magnetic stirrer until there are no particles, thus obtaining a spinning solution containing TPECNPy-2. Set the voltage to 13kV, perform electrostatic spinning on the spinning solution, set the propulsion rate to 1mL / h, and spin for 2h to obtain micro-nano fluorescent fibers containing TPECNPy-2.
[0101] Example 3
[0102] This embodiment provides a method for preparing a fluorescent material TPECNPy-3, the steps are:
[0103] Weigh tetraphenylethylene monoaldehyde (2.00 g, 5.54 mmol) and 3-acetonitrile pyridine (0.74 g, 6.38 mmol) in a three-necked flask and dissolve them. Add 40 mL of ethanol to fully dissolve them. Add 0.5 ml of tetrabutylammonium hydroxide (0.8 M methanol solution) and stir to react for 6 hours. Stop the reaction, filter under reduced pressure, wash the product with ethanol 3 times until the washing liquid is relatively clear, scrape off the sample powder and put it in an oven to dry. Finally, weigh 2.04 g of light yellow solid, with a yield of 73.6%. The synthetic route of the fluorescent material in this embodiment is as follows: Figure 1 As shown in the mass spectrum Fig.13 As shown, the test results of the product obtained in this embodiment are: 1H NMR (600MHz, DMSO-d6) δ8.92(s,1H),8.58(s,1H),8.18–7.89(m,2H),7.74(d,J=8.0Hz,2H),7.53(s,1H),7.09(ddt,J=85.1,20.3,9.0Hz,16H).
[0104] 13 C NMR (151MHz, DMSO-d6) δ150.34,147.23,143.30,133.76,131.96,131.77,131.19,131.07,129.34,128.51,128.34,124.40.
[0105] EI-MS,m / z:460([M] + ,calcd for C 34 H 24 N2,460). It can be seen that the fluorescent material shown in Formula II was prepared in this embodiment.
[0106] Example 4
[0107] This embodiment provides a method for preparing micro-nano fluorescent fibers using TPECNPy-3 prepared in Example 2 as a preparation raw material, the steps are:
[0108] Prepare a spinning solution containing TPECNPy-3 sample: weigh DMF:DCM=1:2 as solvent, add 19% of cellulose acetate powder to dissolve, and completely dissolve the prepared solution in a magnetic stirrer until there are no particles, thus obtaining a spinning solution containing TPECNPy-3. Set the voltage to 13kV, perform electrostatic spinning on the spinning solution, set the propulsion rate to 1mL / h, and spin for 2h to obtain micro-nano fluorescent fibers containing TPECNPy-3.
[0109] Comparative Example 1
[0110] This comparative example provides a method for preparing a fluorescent material TPECNPy-2. The difference from Example 1 is that the reaction time of this comparative example is 3 h, 2.15 g of light yellow solid is weighed, and the final yield is 47%.
[0111] Comparative Example 2
[0112] This comparative example provides a method for preparing a fluorescent material TPECNPy-2. The difference from Example 2 is that the addition amount of cellulose acetate in this comparative example is 25% of the total mass ratio of the spinning solution, and the spinning effect is poor or even no spinning can be performed.
[0113] Test Case
[0114] Aggregation-induced emission effect (AIE) performance test
[0115] Fluorescent materials with different water contents were placed in a fluorescence spectrometer for testing. The excitation wavelength was 365 nm and the wavelength range was set to 400-700 nm. Using tetrahydrofuran (THF) as solvent, 0.0051 g of the pure target product was taken and 50 mL of a 2.0×10 -4 mol / L mother solution, prepare sample solutions according to the water content of 0%-90%. First, use a pipette to take 1mL of mother solution into a 10mL clean test tube. According to the required sample solution concentration, add THF first and then pure water. For example, for a sample solution with a water content of 20%, add 1mL of mother solution, 7mL of THF and 2mL of pure water.
[0116] like Figure 2 As shown in the figure, when only the good solvent THF exists, the fluorescence emission of the TPECNPy / THF solution is very weak and almost invisible to the naked eye; when the water content is lower than 70%, the fluorescence spectrum does not change much. On the contrary, when the water content reaches 90%, the fluorescence intensity increases sharply, increasing by 18 and 10 times respectively compared with its fluorescence intensity in pure THF solution.
[0117] Using the UV-Vis absorption spectroscopy method, samples with different water contents were placed in a UV-Vis photometer for testing, wherein the reference solution was ultrapure water and the wavelength range was set to 400-800 nm.
[0118] The results are as follows Figure 3 , Figure 4 and Figure 5 As shown in the figure, the optical absorption properties of TPECNPy / THF / H2O solutions with different water contents are similar in absorption spectra from 0% to 70% solution, with no significant changes. However, when the water content is greater than 70%, the UV-visible spectrum will show tailing caused by Mie scattering (Mie) effect at long wavelengths. Figures 2 to 5 As is known, the rapid increase in the fluorescence of the mixed solution is due to the formation of nano-aggregates, that is, the synthesized compounds all have aggregation-induced emission effect, which can be further applied in the fields of fluorescent probes.
[0119] Mechanical force stimulation response performance test
[0120] The original sample of TPECNPy synthesized from 2-acetonitrilepyridine is a light yellow powder under visible light, and exhibits blue-green fluorescence under ultraviolet light (365nm); after the initial sample is fully ground, an obvious color change can be seen under visible light, and the sample becomes dark yellow, and exhibits dark yellow fluorescence under ultraviolet light; solid fluorescence tests of the samples before and after grinding found that the maximum fluorescence emission wavelength of the initial sample was 479nm, while the maximum emission wavelength of the sample after grinding was 508nm, a red shift of 29nm. The ground samples were then annealed and fumigated with CH2Cl2 solvent, and it was found that the maximum fluorescence emission wavelength of the samples showed a blue shift, and it just returned to a position similar to the sample before grinding. From the apparent color point of view, the apparent color and fluorescence of the three samples showed consistent behavior. The results are as follows Figure 6 As shown, TPECNPy-2 has good pressed color change performance and good reversible performance.
[0121] The original sample of TPECNPy synthesized from 3-acetonitrilepyridine is a light yellow powder under visible light, light blue under ultraviolet light, dark yellow under ultraviolet light after grinding, and green fluorescence under ultraviolet light. Solid fluorescence tests were also performed on the samples before and after grinding. The maximum emission wavelength of the 3-pyridine sample was 474nm, and the maximum fluorescence emission wavelength of the ground sample was 500nm, which was 26nm red-shifted. The ground samples were then annealed and fumigated with CH2Cl2 solvent. It was found that the maximum fluorescence emission wavelength of the sample showed a blue shift, and it just returned to a position similar to the sample before grinding. From the apparent color point of view, the apparent color and fluorescence of the three samples showed consistent behavior. The results are as follows Figure 6 As shown, TPECNPy-3 has good pressed color change performance and good reversible performance.
[0122] Acid stimulation response performance test
[0123] The initial samples of the two TPECNPy were acid-fumigated with hydrochloric acid, as Figure 5 As shown in the figure, both samples showed obvious color changes. The fluorescence of the initial acid-fumigated sample of TPECNPy-2 changed from light blue to dark yellow, while the fluorescence of the initial acid-fumigated sample of TPECNPy-3 showed blue-green. The degree of reaction between the two samples with acid was obviously different. Figure 5 It can be seen that the red shift of the initial sample of TPECNPy-2 is greater than that of TPECNPy-3.
[0124] The results are as follows Figure 7As shown, the maximum emission wavelength of the initial sample of TPECNPy-2 is 483nm, while the maximum emission wavelength of the sample after acid fumigation is 556nm, which is 73nm red-shifted. The fluorescence color of solid fumigated ammonia vapor (O-HCl-NH3) is restored to blue, and its fluorescence spectrum is almost restored to the original powder state. TPECNPy-2 has obvious acid-base stimulus response characteristics. The maximum emission wavelength of the initial sample of TPECNPy-3 is 474nm, while the maximum emission wavelength of the sample after acid fumigation is 495nm, which is 21nm red-shifted. The fluorescence color of solid fumigated ammonia vapor (O-HCl-NH3) is restored to blue, and its fluorescence spectrum is almost restored to the original powder state. TPECNPy-3 has obvious acid-base stimulus response characteristics.
[0125] The ground initial samples of the two TPECNPy were acid-fumigated using hydrochloric acid, as Figure 8 As shown, both samples showed obvious color changes. The maximum emission wavelength of the initial TPECNPy-2 sample was 508nm, while the maximum emission wavelength of the acid-fumigated sample was 589nm, which was 81nm red-shifted. The fluorescence color of the solid fumigated ammonia vapor (G-HCl-NH3) was restored, and its fluorescence spectrum was almost restored to the original powder state. TPECNPy-2 still had obvious acid-base stimulus response characteristics after grinding.
[0126] The maximum emission wavelength of the initial TPECNPy-3 sample is 492nm, while the maximum emission wavelength of the acid-fumigated sample is 553nm, which is 61nm red-shifted. The fluorescence color of the solid fumigated ammonia vapor (G-HCl-NH3) is restored, and its fluorescence spectrum is almost restored to the original powder state. TPECNPy-3 still has obvious acid-base stimulus response characteristics after grinding.
[0127] Acid-base stimulation response performance test of micro-nano fluorescent fiber membrane
[0128] The acid-base induced color change test was used, and the results were as follows Fig. 9 , Fig.10 and Fig.11As shown, the nanofiber membrane (mh) was fumigated with hydrogen chloride gas, and the membranes (m) with 0.1wt% TPECNPy-2 and TPECNPy-3 showed orange fluorescence and yellow fluorescence, respectively, with emission peaks at 617nm and 562nm, respectively, which were red-shifted by 112nm and 64nm compared with the original membrane (m). The fluorescence color of the TPECNPy-2 and TPECNPy-3 nanofiber membranes fumigated with ammonia vapor (mhn) was restored to light green, and their fluorescence spectra were almost restored to the original powder state. TPECNPy-2 and TPECNPy-3 retained the acid-base stimulus response even when the amount added was very small. The acid-base color change of the micro-nano fluorescent fiber membrane showed that it had good application potential in fluorescent membrane sensors. The nanofiber membrane obtained by electrospinning, a simple and efficient technology, has expanded the application of TPECNPy in real life and also provided another efficient strategy for fluorescent film sensors.
[0129] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A fluorescent material, characterized in that: The fluorescent material is selected from at least one of TPECNPy-2 and TPECNPy-3; the structural formula of the TPECNPy-2 is shown in I, and the structural formula of the TPECNPy-3 is shown in II: ; The maximum emission wavelength of solid-state fluorescence of the TPECNPy-2 is 479 nm; The maximum emission wavelength of solid-state fluorescence of the TPECNPy-3 is 474 nm.
2. A method for preparing the fluorescent material as claimed in claim 1, characterized in that: The following steps are involved: The tetraphenylethylene aldehyde is mixed with a pyridine source and reacted under the catalysis of tetrabutylammonium hydroxide; The pyridine source is selected from at least one of 2-acetonitrile pyridine and 3-acetonitrile pyridine.
3. The preparation method according to claim 2, characterized in that: The molar ratio of the tetraphenylethylene monoaldehyde to the pyridine source is 1:1-1.
2.
4. A micro-nano fluorescent fiber, characterized in that: The raw materials for preparing the micro-nano fluorescent fibers include the fluorescent material described in claim 1.
5. The micro-nano fluorescent fiber according to claim 4, characterized in that: The raw materials for preparing the micro-nano fluorescent fibers also include cellulose acetate and a solvent.
6. A method for preparing micro-nano fluorescent fibers as claimed in claim 4 or 5, characterized in that: The following steps are involved: The fluorescent material, cellulose acetate and solvent are mixed to form a spinning solution, and the micro-nano fluorescent fiber is prepared by electrostatic spinning technology.
7. The method for preparing micro-nano fluorescent fibers according to claim 6, characterized in that: The parameters of the electrospinning technology are set as follows: the spinning voltage is 13KV~17KV; the propulsion rate is 1mL / h~2mL / h; and the curing distance from the needle to the receiving screen is 10~15cm.
Citation Information
Patent Citations
Fluorescent material and application thereof
CN114315732A